Geological controls on gold grade distribution in Chidlaw Link Zone, Gwynfynydd mine, Dolgellau, north Wales - G. S. Camm (The Institute of Materials, Minerals and Mining, 1905)
Gwynfynydd is a small, high-grade black shale-hosted vein-gold deposit. The Chidlaw Link Zone is the only area being mined and contains 24 000 t ore grading 15.2 g/t gold. Within the Link Zone a complex vein structure occurs consisting of a mother vein up to 5 m thick and narrow (less than 0.5 m) leader veins. The former shows minor variations in dip, strike and thickness, whereas the latter show marked changes in all three. The leader veins are hosted within the footwall zone of the mother vein and both are composed of quartz with galena, sphalerite, chalcopyrite, pyrite and minor arsenopyrite. The vein system is transected by a series of cross-vein and intra-vein dip-slip faults. Pockets of gold occur at vein intersections or branches and within the complex footwall zone and are often related to variations in vein attitude and/or geometry. The Chidlaw Link Zone displays a complex, erratic distribution of gold mineralisation and a multi-stage history of structural activity, fluid flow and mineral deposition